Case Report: Perianal infection in children caused by ingested jujube pits: a report of two cases - Jiang, Guoping; Wu, Lixu; Ruan, Weiwei; Shao, Qian; Zhu, JianMing (Frontiers in Pediatrics, 2024)
The ingestion of jujube pits by children is a rare cause of perianal infection.This article aimed to report two cases of perianal infection in children resulting from the ingestion of jujube pits. Methods: We reviewed the clinical records of perianal infection caused by jujube pits at our hospital. Details of the patients' presentation, imaging studies, complications and treatment were recorded. Results: Both pediatric patients presented with perianal swelling and pain. The caregivers of both patients denied a history of jujube consumption. Magnetic resonance imaging (MRI) indicated the presence of jujube pits, which were subsequently removed during surgery. Postoperatively, both patients recovered well, and follow-up showed no recurrence or the formation of anal fistulas.The ingestion of jujube pits leading to perianal infection is rare and inconspicuous. Early diagnosis and treatment are beneficial in preventing the occurrence of serious complications.